Regional Status of Implementing Food and Nutrition Security Plans - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
Presentation on theme 1: Insights into Challenges in Food and Nutrition Security